2016
DOI: 10.1073/pnas.1613891113
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic-nucleotide–gated cation current and Ca2+-activated Cl current elicited by odorant in vertebrate olfactory receptor neurons

Abstract: Olfactory transduction in vertebrate olfactory receptor neurons (ORNs) involves primarily a cAMP-signaling cascade that leads to the opening of cyclic-nucleotide-gated (CNG), nonselective cation channels. The consequent Ca 2+ influx triggers adaptation but also signal amplification, the latter by opening a Ca 2+ -activated Cl channel (ANO2) to elicit, unusually, an inward Cl current. Hence the olfactory response has inward CNG and Cl components that are in rapid succession and not easily separable. We report h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 69 publications
2
27
2
Order By: Relevance
“…2D, E). These results suggest that EOGs in Ano2 À/À mice originate from CNG channels and not from a CNG/Cl À channel combination as in wild-type mice Li et al 2016).…”
Section: Afferent Signal Amplification By Anoctaminmentioning
confidence: 70%
See 1 more Smart Citation
“…2D, E). These results suggest that EOGs in Ano2 À/À mice originate from CNG channels and not from a CNG/Cl À channel combination as in wild-type mice Li et al 2016).…”
Section: Afferent Signal Amplification By Anoctaminmentioning
confidence: 70%
“…Additional information for understanding Cl À -based signal amplification came from single-ORN recordings. A recently developed method makes it possible to separate quantitatively cation currents from chloride currents during odor response (Li et al 2016). The study demonstrated that the ratio of currents through Ca 2+ -gated Cl À channels and CNG channels, I Cl /I cation , increased at low odor concentrations, an observation consistent with our finding that ANO2-mediated amplification is strongest at low stimulus intensities.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the Cl − current is the predominant component of the currents that depolarize ORNs [39,58] and is mediated by Ca 2+ -gated Cl − ion channels. This current response induced due to Ca 2+ is again a Hill function of coefficient greater than one, suggesting further cooperativity [81].…”
Section: Competitive Bindingmentioning
confidence: 99%
“…Recently, we have developed in frog ORNs a protocol that successfully dissects the overall olfactory response into its CNG and Cl components (29). We found that, at least in frog, the Cl current is the major component throughout the dynamic range of the response, including near action-potential-signaling threshold to the brain (29).…”
mentioning
confidence: 99%